Unique Abnormalities in Right Ventricular Longitudinal Strain in Systemic Sclerosis Patients. (June 2016) - Mukherjee, Monica; Chung, Shang-En; Ton, Von Khue; Tedford, Ryan J.; Hummers, Laura K.; Wigley, Fredrick M.; Abraham, Theodore P.; Shah, Ami A.
Abstract : Background—: Cardiac involvement in systemic sclerosis (scleroderma [SSc]) adversely affects long-term prognosis, often remaining undetectable despite close clinical examination and 2-dimensional echocardiographic monitoring. Speckle-derived strain of the right ventricle (RV) was utilized to detect occult abnormalities in regional and global contractility in SSc patients. Methods and Results—: A total of 138 SSc patients with technically adequate echocardiograms was studied and compared with 40 age- and sex-matched healthy non-SSc controls. Standard assessment of RV chamber function included tricuspid annular plane systolic excursion and fractional area change. RV longitudinal systolic speckle-derived strain was assessed in the basal, mid, and apical free wall. Tricuspid annular plane systolic excursion was not different between groups ( P =0.307). Although fractional area change was lower in SSc patients than in controls (mean, 48.9 versus 55; P =0.002), the mean fractional area change was still within the normal range (>35). In contrast, RV longitudinal systolic speckle-derived strain measures were significantly different between groups, both globally (−20.4% versus −17.7%; P =0.005) and regionally: they were decreased in the apex (−8.5% versus −17.1%; P <0.0001) and mid segments (−12.4% versus -20.9%; P <0.0001), and increased in the base (−32.2% versus −23.3%; P =0.0001) for the SSc group. The regional difference in the base compared with the apex was significantly greater for SSc than for controls ( P <0.0001 for interaction). The differences observed in regional strain between SSc and control were unchanged after adjusting for RV systolic pressure. Conclusions—: Speckle-derived strain reveals a heterogenous pattern of regional heart strain in SSc that is not detected by conventional measures of function, suggestive of occult RV myocardial disease. Abstract : Supplemental Digital Content is available in the text.